2012
DOI: 10.1111/j.1467-6494.2011.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Cognitive View of Trait Mindfulness: Distinct Cognitive Skills Predict Its Observing and Nonreactivity Facets

Abstract: Dispositional variations in mindfulness and its facets have garnered considerable recent interest in the clinical and personality literatures. Theoretically, high mindful individuals have been characterized as more attuned to momentary sensations and perceptions and/or better able to execute behavior in a controlled manner, yet data of this relatively cognitive type have not been reported. In addition, perceptual attunement and executive control are distinct skills that may underlie, or at least correlate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
81
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 60 publications
(151 reference statements)
10
81
7
Order By: Relevance
“…Further escalation of the emotional experience through secondary emotional reactions would be less likely in highly mindful individuals resulting in a memory that is harder to retrieve intentionally in response to emotion cue words of the kind used in the AMT. Consistent with this suggestion, Anicha, Ode, Moeller and Robinson (2012) reported that individuals who scored high in the observing (presence), but not nonreactivity (acceptance), facet of dispositional mindfulness showed greater perceptual abilities in two different perceptual tasks.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Further escalation of the emotional experience through secondary emotional reactions would be less likely in highly mindful individuals resulting in a memory that is harder to retrieve intentionally in response to emotion cue words of the kind used in the AMT. Consistent with this suggestion, Anicha, Ode, Moeller and Robinson (2012) reported that individuals who scored high in the observing (presence), but not nonreactivity (acceptance), facet of dispositional mindfulness showed greater perceptual abilities in two different perceptual tasks.…”
Section: Discussionmentioning
confidence: 53%
“…One is the reliance on self-report to measure trait mindfulness. To date there is no consensus on a valid psychometric measure of dispositional mindfulness (Anicha et al 2012). The FMI was used in this study because it is sensitive to variations in meditation experience (Walach et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, both the describe facet and the ability to allow sensations, cognitions and emotions to come and go, without getting caught up in them (non-reactivity facet) may likely be better predictors of an individual's cognitive attributes, such as flexible cognitive control (see Anicha, Ode, Moeller, & Robinson, 2012) than variables that explain general life stress.…”
Section: Discussionmentioning
confidence: 99%
“…This is a novel finding, and we suggest that it is in accordance with several theoretical formulations and with a number of previous empirical studies that have investigated mindfulness and aesthetic experience separately. Observing is widely regarded as a key feature of mindfulness (Bishop et al, 2004;Lilja, Lundh, Josefsson, & Kalkenstrőm, 2012), and experimental evidence suggests that the Observing facet of trait mindfulness appears to be related in particular to perceptual awareness (Anicha et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, when attention is focused on present moment experience, there should follow a greater sensitivity and receptivity to sense perceptions, that may enhance the capacity to perceptually engage with and respond more deeply to a work of art (Anicha, Ode, Moeller, & Robinson, 2012). Several influential information-processing accounts of aesthetic experience highlight the pivotal role of perceptual processing and attentional mechanisms in the generation of the aesthetic response (Chatterjee, 2011;Cupchik & Winston, 1996;Leder, Belko, Oeberst, & Augustin, 2004;Marković, 2012).…”
Section: Introductionmentioning
confidence: 99%